Insurance: Its Role in Recovery from the 2010–2011 Canterbury Earthquake Sequence. Issue 1 (February 2014) - King, Andrew; Middleton, David; Brown, Charlotte; Johnston, David; Johal, Sarb
Earthquakes generate loss only when assets are near enough to be significantly shaken. When communities are highly insured, much of that loss transfers to the insurer. Many events in the 2010–2011 Canterbury Earthquake Sequence were sufficiently shallow and close to (or under) Christchurch to subject the city to very intense shaking (V: 1.7 g; H: 2.2 g). Shaking damage was extensive, exacerbated by the city's setting wherein the eastern suburbs were built on low-lying flatlands (formerly swamp) where liquefaction was widespread, and the southern suburbs, on the flanks of the now-dormant Lyttelton/Akaroa volcano, experienced boulder roll and landslide effects. There were 17 events in the sequence that resulted in insurance claims. The interval between damaging events was insufficient to enable the widespread damage to be assessed or repaired. Furthermore, the combination of tectonic subsidence and liquefaction ejectile lowered the land surface, creating unacceptable flood risk. This paper provides a snapshot of the most complicated insurance settlement program experienced anywhere.